Floating Wetlands: A Sustainable Tool for Wastewater Treatment. Issue 10 (6th September 2018) - Shahid, Munazzam Jawad; Arslan, Muhammad; Ali, Shafaqat; Siddique, Muhammad; Afzal, Muhammad
Abstract : Floating treatment wetland (FTW) is an effective and sustainable technology for wastewater treatment. It has been widely adopted for treating various kinds of polluted water including agricultural runoff, stormwater, industrial effluents, etc. In FTWs, plants are vegetated on a floating mat while their roots are extended down to the contaminated water hence acting as biological filters. Nutrients and potentially toxic metal(s)/element(s) are taken up from the wastewater by plants through their roots whereas organic matter is degraded by the microorganisms forming biofilms on the roots and mat surface. Additionally, organic contaminants which are already taken up by the plants are degraded by endophytic bacteria in planta . This article provides an overview of FTWs and their application for wastewater treatment. The key factors which have an impact on the performance of FTWs are also described. Lastly, the potential role of combined use of plants and bacteria in FTWs for the maximum remediation of polluted water is emphasized. Abstract : Floating treatment wetlands can be exploited to treat various kinds of polluted water. In this system, plants are vegetated on a floating mat and their roots are extended down to the contaminated water acting as biological filters. The plants take up nutrients and trace metals whereas microorganisms degrade organic matter.